AETIOLOGICAL FACTORS OF CHRONIC LIVER DISEASE IN CHILDREN - Tahir, Awais; Malik, Faisal Raza; Ahmad, Iftikhar; Krishin, Jai; Akhtar, Parveen (Journal of Ayub Medical College Abbottabad, 2011)
Background: Chronicity of liver disease is determined either by duration of liver disease or by evidence of either severe liver disease or physical stigmata of chronic liver disease. Chronic liver disease may be caused commonly by persistent viral infections, metabolic diseases, drugs, autoimmune hepatitis, or unknown factors. The objective of this study was to find out the aetiology of chronic liver disease (CLD) in children. Methodology: It was a descriptive, prospective study which used a structured proforma designed to collect data of cases of CLD from both indoor and outdoor Paediatrics units of Fauji Foundation Hospital, Rawalpindi, and Children Hospital, Pakistan Institute of Medical Sciences, Islamabad. All children under 12 years having either clinical or biochemical evidence of liver disease and/or elevated liver enzymes for more than 3 months were included in this study. Results: Sixty cases of CLD were enrolled from indoor and outdoor units from January 2010 to July 2011. Thirty-nine (65%) cases were male and 21 (35%) were female. Eleven children were less than 1 year, 18 were 1-5 years old and 31 were 5-12 years of age. Viral hepatitis was the most common cause found in 22 (36.7%) cases. Out of these 22 patients with viral aetiology 19 (31.66%) patients had Hepatitis C and 3 (5%) had Hepatitis B. Glycogen storage disease was seen in 8.3% cases, and biliary atresia and Wilson disease in 6.7% each. Other less commonly found cases were autoimmune hepatitis, TORCH infections, hepatoma and drug induced hepatitis (1.7% each). Cause couldn’t be established in 35% cases which remained idiopathic. Conclusion: Viral hepatitis is the leading cause of chronic liver disease in children, with the highest incidence of chronic Hepatitis C followed by metabolic disorders (glycogen storage disease and Wilson disease) and biliary atresia. Chronic viral hepatitis was most prevalent between 11 months to 12 years of age. Wilson disease was common in 3-7 years age group, and Biliary atresia in 4-7 months age group. Glycogen storage disease was prevalent between 5 months to 3 years. Keywords: Chronic liver disease, Chronic viral hepatitis, Wilson disease